Perancangan Sistem Informasi Manajemen Pemesanan Barang Berbasis Online Menggunakan Pendekatan Extreme Programming - Adhie Thyo Priandika; Doni Riswanda (Jurnal Ilmiah Computer Science, 2023)
The design of an online goods order management information system facilitates the process of ordering goods more effectively and efficiently because it is done computerized, customers do not need to come far to the store to order goods because it can be done anywhere and anytime. With the management application for ordering goods at donnys stores using the PHP programming language, dreamwever applications are designed with UML (Unified Modeling Language) system development tools and use extreme programming development methods, and use MySQL databases, for program testing using ISO 25010. So that it can facilitate the delivery of information and control the inventory of goods. The test results above show that the application is made in accordance with the functionality aspect of 95% and the usability aspect of 96%, so that the application is made according to the needs and can facilitate the process of ordering goods online.